Cyst and endometriosis of the canal of Nuck: rare differentials for a female groin mass. Issue 1 (22nd January 2022) - Hwang, Bridget; Bultitude, Jacqueline; Diab, Jason; Bean, Andrew
Abstract: Cyst of the canal of Nuck is a rare abnormality of the female inguinal canal that can present similarly to a hernia. If incompletely obliterated, the patent canal of Nuck may predispose to an inguinal hernia or hydrocele due to direct communication with the abdominal cavity. Such defects are normally detected and repaired in early childhood but can also present later in adult life. We report the case of a 44-year-old woman who presents with a fluctuant, mobile and irreducible left-sided groin mass. Ultrasound of the groin identified a cystic structure in the canal of Nuck. The patient underwent successful open herniorrhaphy with excision of the cyst and mesh repair of the inguinal canal. Subsequent histopathological examination also revealed concurrent endometriosis of the canal of Nuck. A systematic approach to differential diagnoses for a female groin mass, further investigations and management are discussed.